Efisiensi Sistem Pembayaran Cashless: Dampak Penggunaan QRIS terhadap Akuntabilitas Keuangan pada Bisnis Kuliner Skala Kecil - Kurniawan, Sena; Sarah, Yuni Siti (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines how the efficiency of the QRIS cashless payment system affects the financial accountability of small-scale culinary businesses. This study employed a quantitative approach with an explanatory survey method. Data collection utilized purposive sampling, involving 115 active culinary MSMEs. The measurement instrument adopted the Technology Acceptance Model (TAM) framework. Furthermore, the data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) via SmartPLS 4.0 software. The findings show that the efficiency of the QRIS system, characterized by perceived ease of use, usefulness in accelerating transactions, and digital footprint security, has a positive and significant effect on financial accountability. The structural model demonstrates a predictive relevance of 64.2%. Specifically, QRIS implementation effectively nudges micro-entrepreneurs to separate funds, simplifies daily cash reconciliation, and automates basic financial reporting. The study implies that QRIS transcends its primary function as a payment gateway, acting as a vital catalyst in mitigating the “mingling of funds” habit and addressing the “missing middle” financing gap for micro-enterprises. This research suggests that financial service providers should incorporate automated financial statements in merchant apps to enhance MSMEs' creditworthiness.